Using WhatsAppbased mobile learning environments during abrupt switches to online learning: A duoethnographic account - Christa van Staden; Liezel Nel (Perspectives in Education, 2023)
Abrupt switches to online learning without face-to-face contact between facilitators and students can cause distress and have a negative impact on student success. As students use instant messaging applications (IMAs) to communicate with one another, we have integrated WhatsApp-based mobile learning environments (MLEs) in two disparate higher education settings to facilitate learning. Christa used an MLE pre-pandemic in a postgraduate distance education context, while Liezel used several MLEs during the pandemic in an undergraduate contact education context. In this duoethnographic1 account, we share our stories about using these MLEs during times of distress. Duoethnography is a collaborative methodology that allowed us to juxtapose our life histories to create multiple understandings of the phenomenon to learn from one another. With currere as theoretical framework, we employed storytelling to compare our life histories, educational contexts and beliefs while we illustrate a sense of personal change. In addition to sharing our insights regarding the affordances and challenges related to WhatsApp-based MLEs, we illustrate how this dialogic methodology facilitated dialogue and reflection – affording two educational researchers in disparate higher education contexts deeper insights regarding their own practices.